Adaptation to Complex Pictures: Exposure to Emotional Valence Induces Assimilative Aftereffects - Palumbo, Rocco; D’Ascenzo, Stefania; Quercia, Angelica; Tommasi, Luca (Frontiers in Psychology, 2017)
Aftereffects have been documented for a variety of perceptual categories spanning from body gender to facial emotion, thus becoming an important tool in the study of high-level vision and its neural bases. We examined whether the perceived valence of a complex scene is subject to aftereffects, by observing the participants’ evaluation of the valence of a test picture preceded by a different picture. For this study, we employed an adaptation paradigm with positive and negative images used as adapters, and positive, negative, and neutral images used as tests. Our results show that adaptation to complex emotional pictures induces assimilative aftereffects: participants judged neutral tests more positively following positive adapters and more negatively following negative adapters. This depended on the prolonged adaptation phase (10 sec), as the results of a second experiment, in which adapters lasted for 500 msec, did not show aftereffects. In addition, the results show that assimilative aftereffects of negative and positive adapters also manifested themselves on non-neutral (negative and positive) targets, providing evidence that the global emotional content of complex pictures is suitable to induce assimilative aftereffects.